BUSINESS ANALYSIS OF FISHING A CRAB (Portunus Pelagicus) AT EAST BINTAN SUBDISTRICT BINTAN DISTRICT REGENCY RIAU ISLAND PROVINCE - Eko Hadi Partoyo; Zulkarnaini Zulkarnaini; Hendrik Hendrik (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research about business analysis of Fishing a crab (Portunus Pelagicus) held on APRIL 2017 at Est Bintan SubDistrict Bintan District regency Riau Island province. This research aim to (1) calculates how much capital investment business catching crab(2) analysis expediency buainess of catching a crab (Portunus Pelagicus). Method used in this research was survey method which involve observation, interview, and documentation.Based on research result (1) average of total investment in the crab fishing business by applying the fishing gear in the East Bintan district Bintan province Riau archipelago average investment trunks with a business unit 100> IDR. 90,671,250 for business unit 51-100 investment in planting of IDR. 64.212.000 while for business unit <50 eat invested that is equal to IDR. 32.010.000. (2) business of catching a crab at coastal East Bintan was decent whit RCR value>1, whith FRR value>6,1 % and PPC value between 1,38-1,62 per period or ±1 year and 3 month. Keywords: Fishing of Crab, Business Analysis, East Bintan Subdistrict